Exploring the contribution of mentoring practices to mentee learning in a Malaysian youth development programme - Lee, Kwan Meng; Krauss, Steven Eric; Suandi, Turiman; Hamzah, Azimi (Routledge, 2016)
Within the mentoring relationship, it is generally accepted that learning takes place through the sharing and transmitting of knowledge between mentor and mentee, where mentors employ practices such as coaching, facilitation, guidance and reflection on experiences. Despite the number of studies on mentoring in the context of youth development programmes, mentoring relationship processes in youth development contexts is not well understood. Few studies have examined the variety of practices used by mentors and explored their contributions to different types of mentee learning. In an attempt to better understand this relationship, an exploratory correlational study was conducted on a group of youth development programme participants from Malaysia (N = 90) to identify how various mentoring practices enhance learning. The results showed that overall, facilitation and coaching contributed the most to new learning. While coaching showed the highest contribution to skill acquisition and knowledge learning, the contribution of facilitation was mainly towards attitude learning. Implications of the findings are discussed.